2001
DOI: 10.1063/1.1371539
|View full text |Cite
|
Sign up to set email alerts
|

Growth of high-quality GaN on Si(111) substrate by ultrahigh vacuum chemical vapor deposition

Abstract: An ultrahigh vacuum chemical vapor deposition (UHVCVD) system was employed to grow high-quality GaN on a Si (111) substrate using a thin AlN buffer layer. X-ray diffraction, high-resolution electron microscopy (HREM), and photoluminescence (PL) data indicate that a single crystalline GaN layer with a wurtzite structure was epitaxially grown on a silicon substrate. The full width at half maximum (FWHM) of the x-ray rocking curve for the GaN (0002) diffraction was 16.7 arc min. A cross-sectional HREM image showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The full width at half maximum (FWHM) values of (0 0 0 2) and (1 0 1 2) diffraction are 13.7 and 35.3 arcmin, respectively. The FWHM value of (0 0 02) diffraction is even less than the reported values in a range from 14.7 to 18.8 arcmin, as observed from GaN/Si(1 1 1) by MOCVD [18,19] and ultrahigh vaccum chemical vapor deposition [13]. The rocking curves of symmetric planes are normally responsive to mosaic distortions but insensitive to the pure edge threading dislocations (TDs) because these planes are undistorted by pure edge TDs [18,20].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The full width at half maximum (FWHM) values of (0 0 0 2) and (1 0 1 2) diffraction are 13.7 and 35.3 arcmin, respectively. The FWHM value of (0 0 02) diffraction is even less than the reported values in a range from 14.7 to 18.8 arcmin, as observed from GaN/Si(1 1 1) by MOCVD [18,19] and ultrahigh vaccum chemical vapor deposition [13]. The rocking curves of symmetric planes are normally responsive to mosaic distortions but insensitive to the pure edge threading dislocations (TDs) because these planes are undistorted by pure edge TDs [18,20].…”
Section: Resultsmentioning
confidence: 85%
“…A variety of interlayers between GaN epilayers and the sapphire substrate have been grown to reduce dislocations and/or cracks in GaN layer [9][10][11][12]. Recent experimental results have concluded that an AlN buffer layer can alleviate the difficulties of GaN growth on Si [13][14][15]. GaN-based light emitting diodes have already been reported on the Si(1 1 1) substrate [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…The origin of the band edge emission peak is well known from earlier experiments and the band edge emission region is mainly dominated by free exciton transition, donor-to-valence band transition and donorbound exciton transitions, among others. [14][15][16] In addition, the thermal broadening, defect related disorder and impurities levels in the GaN film also increases the broadening of the band edge emission peak. Another peak in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wide-band gap gallium nitride (GaN) and III-V nitride groups have been considered as very promising materials for their potential use in UV photodetectors, laser diodes, high-speed field-effect transistors, and high-frequency/power/ temperature electronic devices [1][2][3][4]. They have attracted much attention after the successful fabrication of high-efficiency blue light-emitting diodes and laser diodes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%